The Humility Problem and Imminent Ascension of Artificial Intelligence - Anisin, Alexei (Studies in Christian ethics, 2025)
Will artificial intelligence end up dominating its creators? This article argues that our relationship with AI technology is constituted by spiritual problems and if our imperfections are not critically reflected upon, the aggregate risk of AI will grow to be substantial. The danger of AI concerning human society is not in a lack or incorrect application of regulation, but in our innate deficiency of being able to overcome the humility problem—in our failure to acknowledge mistakes and engage in self-reproach. In contrast, AI is programmed to learn from its mistakes through iterative processes which make it increasingly efficient and error-resistant. As AI evolves, its self-driven capacities will permit it to overcome faults, which boldly diverge with humanity's historical tendency to self-righteously justify wrongdoings. There is thus an urgent need for introspection to counter-balance technocratic and materialistic worldviews that idolise AI as a societal saviour and as a synchronous substitute for divine wisdom.